A Case Report of Pleuropulmonary Blastoma Presenting as Tension Pneumothorax - Addanki, Archana; Chaitanya, Krishna; Bartakke, Sandip; Sethuratnam, Srividya (Indian Journal of Medical and Paediatric Oncology, 2017)
Pleuropulmonary blastoma (PPB) is a very rare, highly aggressive, and malignant tumor that originates from either lungs or pleura. It occurs mainly in children aged <5 or 6 years. It has poor prognosis with three different subtypes: cystic (type I), combined cystic and solid (type II), and solid (type III). PPB is treated with aggressive multimodal therapies including surgery and chemotherapy. We present a case of PPB in a 3-year-old girl who presented with tension pneumothorax.
Keywords: Pleuropulmonary blastoma; primary pulmonary tumor; tension pneumothorax